Mediating role of satisfaction in the relationship between motivational needs and Instagram continuance intention among students in selected universities in Malaysia - Jin, Dian (2024)
Instagram, one of the most prevalent social media platforms, has attracted significant attention, especially among university students. Scholars have shown particular interest in understanding the factors that influence Malaysian university students' continued use of social media platforms like Instagram. The primary purpose of this study was to explore the role of satisfaction as a mediator in the relationship between various types of motivational needs and the continued intention to use Instagram. The motivational needs under study included cognitive needs, affective needs, personal integrative needs, social integrative needs, and escape needs. This research built on the foundations of Uses and Gratifications Theory and Expectation-Confirmation Theory. The research adopted a quantitative approach, using questionnaires to gather data from a sample of 384 students drawn from six universities in the Klang Valley, Malaysia—namely, Universiti Malaya, Universiti Putra Malaysia, Universiti Kebangsaan Malaysia, Universiti Teknologi Malaysia, Taylor's University, and UCSI University. The participants were selected using quota sampling. The collected data was then analyzed using partial least squares structural equation modelling. The findings of the study indicated that satisfaction significantly mediated the relationship between cognitive needs and continuance intention, personal integrative needs and continuance intention, and social integrative needs and continuance intention. In other words, the level of satisfaction derived from Instagram use was a significant factor influencing these specific motivational needs and the intention to continue using Instagram. However, the study found no evidence of satisfaction playing a mediating role between affective needs or escape needs and continuance intention. This suggests that these needs did not necessarily influence the decision to continue using Instagram based on the level of satisfaction derived from the platform. These findings have important implications for both theory and practice, particularly in understanding how satisfaction mediates the relationship between motivational needs and continuance intention on social media platforms like Instagram.